(untitled) (International Association of Biologicals and Computational Digest, 2023)
Water-wise landscaping is regarded as an essential landscaping method in countries with water scarcity. Estimating the water demand associated with urban green infrastructure is crucial for the management of water resources and sustainable design in arid campus settings. This study focuses on analyzing urban wise water landscape quantities to help university campus decision-makers reduce urban water consumption and preserve the urban campus water content for asset management and life quality. According to the research, herbaceous flowering plant-only water-efficient landscapes were both significantly more popular and less expensive than other landscape designs. Except for the combination of deciduous and evergreen plants, all water-wise design trends were chosen over water-demanding landscapes.